Continuous self-provided fermentation for microbial lipids production from acetate by using oleaginous yeasts Cryptococcus podzolicus and Trichosporon porosum. (February 2020) - Qian, Xiujuan; Gorte, Olga; Chen, Lin; Zhang, Wenming; Dong, Weiliang; Ma, Jiangfeng; Xin, Fengxue; Jiang, Min; Ochsenreither, Katrin
Abstract: Conversion of acetates, the by-products generated in industrial processes into microbial lipids by using oleaginous yeasts offers a promising alternative for the economic utilization of waste acetates. In this study, two newly isolated oleaginous yeasts Cryptococcus podzolicus DSM 27192 and Trichosporon porosum DSM 27194 were found to be able to grow with acetate as the sole carbon source and tolerate up to 30 g/L of sodium acetate in shake flask fermentation. Furthermore, an automated fed-batch system using acetic acid as both carbon source and buffering agent was designed. By supplementing glucose as the stimulant for microbial growth, lipids contents of 38.8% and 39.7% were obtained by using C. podzolicus DSM 27192 and T. porosum DSM 27194, corresponding to lipids concentrations of 10.4 g/L and 11.5 g/L, respectively. Moreover, the fatty acid compositional profiles of the acetate-derived lipids were similar to those of vegetable oil, suggesting their potential for biodiesel production. Economical analysis showed that acetic acid derived from volatile fatty acids (VFAs) could be potential substrates for industrial microbial lipids production by using C. podzolicus DSM 27192 and T. porosum DSM 27194. Graphical abstract: Image 1 Highlights: Two new oleaginous yeasts exhibited great acetic acid utilization capability. A self-provided fermentation strategy for acetate utilization was designed. Acetate derived substrates perform promising prospect in microbial lipids production.